SYNTHESIS AND CHARACTERIZATION OF MOLECULAR IMPRINTED POLYMERS FOR PHENYLBUTAZONE EXTRACTION - Dang Soni; Selvira Anandia Intan Maulida; Meilia Suherman; Aliqa Azqia Azzahra (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Phenylbutazone is a pharmaceutical substance often added to rheumatic herbs. However, because of the complexity of the matrix caused by the presence of compounds in herbal medicines, the determination of phenylbutazone requires a time-consuming sample preparation process prior to analysis. This study was conducted to develop a specific sorbent that can be used to prepare phenylbutazone in herbal medicine. The performance of phenylbutazone Molecularly Imprinted Polymer (MIP) was evaluated using three distinct porogens (ethanol, methanol, and methanol-chloroform (1:1)) and two polymerization procedures (bulk and precipitation). According to the results of the polymer optimization, the polymer generated by precipitation in methanol-chloroform (1:1) has good sorbent characteristics. FTIR physical characterization revealed complete polymerization. The bulk procedure produces a more physically stable sorbent than the precipitation method does.  Keywords: MIP Performance Evaluation, Phenylbutazone Molecular Imprinted Polymer, Polymer Imprinting Factor